2013
DOI: 10.1016/j.tetlet.2013.05.136
|View full text |Cite
|
Sign up to set email alerts
|

Improved synthesis of N1-substituted orotic acid derivatives

Abstract: An improved method for the synthesis of N1-substituted orotic acid derivatives is reported. The method involves sequential incorporation of nitrogen atoms to the pyrimidine structure from simple starting materials and thus allows the synthesis of N1-substituted orotic acid derivatives with single 15N label at either N-1 or N-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…13 The reported synthesis of N1-substituted orotic acid derivatives is time-consuming and low-yielding (Scheme 1, the combined yield for the synthesis of 1-cyclohexylorotic acid is about 15%). 11,14–18 Furthermore, we have found that the purification of the final orotic acids can be difficult sometimes. In this Letter , we report a convenient and efficient synthesis of N1-substituted orotic acid derivatives from readily available starting material.…”
mentioning
confidence: 99%
“…13 The reported synthesis of N1-substituted orotic acid derivatives is time-consuming and low-yielding (Scheme 1, the combined yield for the synthesis of 1-cyclohexylorotic acid is about 15%). 11,14–18 Furthermore, we have found that the purification of the final orotic acids can be difficult sometimes. In this Letter , we report a convenient and efficient synthesis of N1-substituted orotic acid derivatives from readily available starting material.…”
mentioning
confidence: 99%